NON-NUTRITIVE SUCKING FOR PROCEDURAL PAIN RELIEF IN A PRETERM NEONATE: A NURSING CASE REPORT - Hiwala Lisdayanti; Janatia Anggraini; Meta Puspita Sari; Nurul Dwi Khairani; Masrianah Masrianah; Selvia Zulviani; Adelia Pradita (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2026)
Premature infants admitted to the neonatal intensive care unit are frequently subjected to repeated invasive procedures, placing them at high risk for procedural pain that can adversely affect neurological development if not properly managed. This case report describes the nursing care provided to a premature infant born at 27 weeks’ gestation with a birth weight of 1,100 grams. The assessment revealed that the infant exhibited acute pain responses during invasive procedures, including peripheral intravenous catheter placement and venous blood sampling, characterized by grimacing, high-pitched crying, increased limb movements, and irregular breathing patterns, with a Neonatal Infant Pain Scale score of 7 indicating severe pain. The established nursing diagnoses included acute pain related to stimulation from invasive procedures, evidenced by physiological and behavioral pain indicators; impaired spontaneous ventilation; risk of infection; and impaired gas exchange related to underlying medical conditions such as respiratory failure, metabolic acidosis, grade 1 hyaline membrane disease, hyperbilirubinemia, and anemia. The nursing care plan was developed by applying the Non-Nutritive Sucking technique as the primary non-pharmacological pain intervention, administered consistently before, during, and after each invasive procedure, supplemented by environmental modifications and the use of the nesting position to optimize the neonate’s comfort. Following the intervention, the Neonatal Infant Pain Scale score decreased significantly from 7 to 1, accompanied by a reduction in crying duration, calmer behavior, and stable physiological parameters. This case demonstrates that the Non-Nutritive Sucking technique is a simple, safe, cost-effective, and scientifically supported nursing intervention for reducing procedural pain in preterm infants in an intensive care setting; therefore, its integration into standard neonatal pain management protocols should be considered.